State-of-the-Art Assistive Powered Upper Limb Exoskeletons for Elderly - Kapsalyamov, Akim; Hussain, Shahid; Jamwal, Prashant K. (IEEE Access)
The number of older people is growing rapidly around the world. Ageing process results in reduced or restricted mobility which is essential to perform activities of daily living. Currently, there are numerous powered assistive exoskeletons commercially available as well as are being developed to support and rehabilitate lower limbs. Significant attention is also been given to develop upper limb rehabilitation devices, however the question of what kind of assistive devices can be used by elderly group of people for their upper limbs and what technical characteristics they should incorporate is not properly researched. This paper presents the state of the art of currently available assistive exoskeletons which can be exploited to support the motions of upper limbs of elderly to perform activities of daily living. Mechanism type, degrees of freedom, type actuators and materials selected for the fabrication of these porotypes are presented in detail. Also, the type of control systems utilized for these upper limb exoskeletons are discussed in detail with the insight on the feedback signal methods. A detailed discussion on the challenges in the fields of mechanism development, actuation and control for these upper limb powered exoskeletons is presented with the opportunities for future technological developments.